The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan - Li, Chun-Lin; Yang, Ping-Shih; Wang, Chuan-Chan (Zootaxa, 2017)
The two Sinodiapterna Dellacasa, 1986 (Coleoptera: Scarabaeidae: Aphodiinae: Aphodiini) species from Taiwan, including Sinodiapterna yushana Li & Wang, new species (玉山長盾蜉金龜), are reviewed with descriptions, illustrations, distributional data, and remarks. Both species represent two species groups, namely the S. troitzkyi group and the S. gorodinskiyi group, respectively, within the genus. A key for the identification of adults of Taiwan is provided. An annotated checklist of the genus is provided with the information for each species including literature review, synonymy, distribution, and type locality.